Late Administration of Surfactant May Increase the Risk of Patent Ductus Arteriosus - Canpolat, Fuat Emre; Kadıoğlu Şimşek, Gülsüm; Webbe, James; Büyüktiryaki, Mehmet; Karaçağlar, Nazmiye Bengü; Elbayiyev, Sarkhan; Kanmaz Kutman, H. Gözde (Frontiers in Pediatrics, 2020)
Indroduction: Early rescue surfactant is the most effective way of administering surfactant but many infants still receive surfactant later. Our aim was to explore the association between timing of surfactant administration and the development of patent ductus arteriosus and other neonatal morbidities. Materials and method: This retrospective study analyzed 819 preterm infants under 30 weeks of gestational age and under 1500 grams. Results: Five hundred and ninety three infants received surfactant during the study period, of these 365 received it within 2 hours of life (early group) and 228 received it after two hours (late group). Patent ductus arteriosus was detected in 175 (48%) of the early group and 168 (74%) of the late group, p=0.001. Multinominal logistic regression analysis demonstrated that receiving surfactant after 2 hours of life has a OR 3.5 (2.2-5.64 95 % CI) and a p value of 0.001 for developing patent ductus arteriosus. Conclusion: In this study population we observed that late surfactant administration is associated with increased risk of patent ductus arteriosus.